Décision touchant la sécurité syndicale dans le conflit Ford 1946. (Relations industrielles / Industrial Relations, 1975)
Arbitrage d'un différend entre la Ford Motor Company of Canada Limited et l'Union Internationale des United Automobile, Aircraft and Agricultural Implement Workers of America {U.A.W.-C.LO.)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Index — volume 30 — 1975 (Relations industrielles / Industrial Relations, 1975)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Livres reçus (Relations industrielles / Industrial Relations, 1975)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Livres reçus (Relations industrielles / Industrial Relations, 1975)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Livres reçus (Relations industrielles / Industrial Relations, 1975)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Livres reçus (Relations industrielles / Industrial Relations, 1975)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Publications récentes (Relations industrielles / Industrial Relations, 1975)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Publications récentes (Relations industrielles / Industrial Relations, 1975)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Publications récentes (Relations industrielles / Industrial Relations, 1975)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Publications récentes (Relations industrielles / Industrial Relations, 1975)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Marxian Analysis - Beach, Earl F. (Relations industrielles / Industrial Relations, 1975)
The Marxian System [of economics] has been universally proclaimed to be dynamic. It is therefore of some importance to discover that the analytical framework is static, that it cannot be modified easily, and that it has led to a very wrong conclusion which has been embedded in Marxian thinking. --Author's introduction
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Pros and Cons - Beatty, David M. (Relations industrielles / Industrial Relations, 1975)
In this paper, the author concludes that the collective bargaining model will be able to preserve the most vital features of the intellectual community.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Le management d’aujourd’hui, Savoir organiser, Savoir décider - Beaulieu, Jean-Pierre (Relations industrielles / Industrial Relations, 1975)
This article reviews "Le management d’aujourd’hui, Savoir organiser, Savoir décider" by Gérald Lefebvre.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Motivation and Commitment - Beaulieu, Jean-Pierre (Relations industrielles / Industrial Relations, 1975)
This article reviews "Motivation and Commitment" by Dale Yoder and Herbert G. Heneman.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Effective Situational Diagnosis : A Programmed Learning Text Based on the 3-D Theory - Bélanger, Laurent (Relations industrielles / Industrial Relations, 1975)
This article reviews "Effective Situational Diagnosis : A Programmed Learning Text Based on the 3-D Theory" by W.J. Reddin and R. Stuart-Kotze.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

How to Manage by Objectives - Bélanger, Laurent (Relations industrielles / Industrial Relations, 1975)
This article reviews the book, "How to Manage by Objectives," by John W. Humble.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Les relations de travail à l’usine - Bélanger, Laurent (Relations industrielles / Industrial Relations, 1975)
This article reviews "Les relations de travail à l’usine" by Renaud Sainsaulieu.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Malaise des cadres et critique des solutions proposées : application aux cadres intermédiaires des affaires sociales - Bélanger, Laurent (Relations industrielles / Industrial Relations, 1975)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Organizational Behavior : Critical Incidents and Analysis - Bélanger, Laurent (Relations industrielles / Industrial Relations, 1975)
This article reviews "Organizational Behavior : Critical Incidents and Analysis" by John F. Murray et Thomas J. von Der Embse.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Personnel and Industrial Relations : A Managerial Approach - Bélanger, Laurent (Relations industrielles / Industrial Relations, 1975)
This article reviews "Personnel and Industrial Relations : A Managerial Approach" by John B. Miner and Mary G. Miner.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Les restrictions des prix et des salaires du Ministre Turner - Belzile, Bertrand (Relations industrielles / Industrial Relations, 1975)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Pour une croissance plus stable de la construction - Belzile, Bertrand (Relations industrielles / Industrial Relations, 1975)
This article reviews "Pour une croissance plus stable de la construction" by le Conseil économique du Canada.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Facteurs affectant l’offre de travail : les personnes à faible revenu - Belzile, Bertrand; Larouche, Viateur (Relations industrielles / Industrial Relations, 1975)
Le présent article rend compte en partie d'une recherche visant à évaluer l'impact sur l'offre de travail des parents de familles à faible revenu des régimes publics de sécurité du revenu au Québec. Dans un premier temps, les auteurs font une revue de la littérature sur les taux d'activité, en insistant plus spécialement sur les principaux facteurs qui ont été utilisés dans quelques recherches empiriques sur le sujet. (Ce dernier examen pivote autour d'une excellente opérationnalisation faite récemment par Bowen et Finegan de l'analyse traditionnelle de l'offre du travail.) Dans un deuxième temps, ils s'attardent à quelques facteurs susceptibles d'affecter plus spécifiquement les parents de familles à faible revenu. Ils suggèrent d'abord une définition opérationnelle de chacun de ces facteurs, puis une mesure possible dans le cadre d'une enquête sur le terrain. Enfin, ils formulent l'hypothèse attendue entre chaque facteur et le taux d'activité. En conclusion, ils rapportent quelques résultats de recherches empiriques relativement aux effets de revenu et de substitution.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Motivation au travail des familles à faible revenu : tentative de mesure - Belzile, Bertrand; Larouche, Viateur (Relations industrielles / Industrial Relations, 1975)
Dans cet article, les auteurs visent à rendre opérationnel le modèle de motivation retenu. L'approche utilisée pour obtenir une mesure de la motivation d'un groupe de parents (N — 31) de familles à faible revenu à se trouver un emploi (travailler) ou à ne pas s'en trouver {ne pas travailler) est explicitée. Échantillonnage, cueillette des données et instrument de mesure sont présentés. Finalement, les résultats sont décrits et les auteurs analysent la relation qui existe (pour ce groupe de parents) entre le taux de participation à la main-d'oeuvre et la motivation à y participer.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

La documentation juridique, Références et abréviations - Blouin, Rodrigue (Relations industrielles / Industrial Relations, 1975)
This article reviews "La documentation juridique, Références et abréviations" by E. Caparros et J. Goulet.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

La qualification des cadres hiérarchiques par le Code du travail - Blouin, Rodrigue (Relations industrielles / Industrial Relations, 1975)
L'auteur analyse la méthode par laquelle les commissaires-enquêteurs et le Tribunal du travail déterminent si un employé peut-être qualifié de cadre hiérarchique au sens de l'article lm) 1° duCode du travail. Après avoir présenté sommairement le critère de fond retenu par les tribunaux et son fondement historique, il passe à l'étude des éléments constitutifs de ce critère: l'exercice de l'autorité hiérarchique ; par délégation de l'employeur ; avec liberté de manoeuvre. L'étude est complétée par une présentation de l'exercice de l'autorité hiérarchique à divers palliers d'action.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Labour Relations Law - Blouin, Rodrigue (Relations industrielles / Industrial Relations, 1975)
This article reviews "Labour Relations Law, Cases-Materials and Commentary" from The Labour Relations Law Casebook Group.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Les autorités publiques et le droit à la protection des fonds et autres biens syndicaux - Blouin, Rodrigue (Relations industrielles / Industrial Relations, 1975)
This article reviews "Les autorités publiques et le droit à la protection des fonds et autres biens syndicaux" by the Burea international du travail (Genève).
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Méthode de recherche en droit québécois et canadien - Blouin, Rodrigue (Relations industrielles / Industrial Relations, 1975)
This article reviews "Méthode de recherche en droit québécois et canadien" by Denis LeMay.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Nature et procédure d’adoption de la cotisation syndicale - Blouin, Rodrigue (Relations industrielles / Industrial Relations, 1975)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Répertoire de décisions en application du Code du travail, tome II, Mesures disciplinaires - Blouin, Rodrigue (Relations industrielles / Industrial Relations, 1975)
This article reviews "Répertoire de décisions en application du Code du travail, tome II, Mesures disciplinaires" by J.G. Descôteaux.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Traité de droit administratif canadien et québécois - Blouin, Rodrigue (Relations industrielles / Industrial Relations, 1975)
This article reviews "Traité de droit administratif canadien et québécois" by René Dussault.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Industrialism and Industrial Man Reconsidered - Boivin, Jean (Relations industrielles / Industrial Relations, 1975)
This article reviews "Industrialism and Industrial Man Reconsidered" by John T. Dunlop, Frederick H. Harbison, Clark Kerr, and Charles A. Myers.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Labor and Management, the Great Contemporary Issues - Boivin, Jean (Relations industrielles / Industrial Relations, 1975)
This article reviews the New York Times article "Labor and Management, the Great Contemporary Issues" by Richard B. Morris.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Public Employee Unionism : Structure, Growth, Policy - Boivin, Jean (Relations industrielles / Industrial Relations, 1975)
This article reviews "Public Employee Unionism : Structure, Growth, Policy" by Jack Stieber.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Quelques cas - Boivin, Jean (Relations industrielles / Industrial Relations, 1975)
Dans cet article l’auteur examine d'abord si le phénomène de syndicalisation ne constitue qu'un feu de paille momentané ou s'il s'inscrit comme une vague de fond qui fauchera l'ensemble des universités canadiennes et américaines d'ici quelques années. Ensuite, l'auteur s'interroge sur la nature des revendications du corps professoral afin de savoir si celles-ci diffèrent de celles mises de l'avant par les autres syndicats.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Strike : A Live History, 1887-1971 - Boivin, Jean (Relations industrielles / Industrial Relations, 1975)
This article reviews "Strike : A Live History, 1887-1971" by R.A. Leeson.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Some Effects of Physician Licensing Requirements on Medical Manpower Flows in Canada - Brown, Malcolm C. (Relations industrielles / Industrial Relations, 1975)
In this paper the author examines the implications of the licensing regulations of physicians in Canada.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Who Wants Collective Bargaining Any Way? - Carrothers, A. W.R. (Relations industrielles / Industrial Relations, 1975)
Collective bargaining in Canada is undergoing strains today, as it has in different circumstances, which are challenging the process and are causing responsible people to question whether it can be improved or should be replaced.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Some Unresolved Dilemmas - Carter, Donald D. (Relations industrielles / Industrial Relations, 1975)
This paper deals with some of the basic problems created by the adoption of collective bargaining procedures by faculty at Canadian colleges and universities.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Confrontation at Winnipeg: Labour, Industrial Relations and the General Strike - Chaison, Gary N. (Relations industrielles / Industrial Relations, 1975)
This article reviews "Confrontation at Winnipeg: Labour, Industrial Relations and the General Strike," by David Jay Bercuson.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Public Sector Bargaining : A Review of A Report or A Tale of Two Persons - Cunningham, William B. (Relations industrielles / Industrial Relations, 1975)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

L’origine de la formule Rand - Dion, Gérard (Relations industrielles / Industrial Relations, 1975)
Trente ans se sont écoulés depuis qu'à l'occasion de la grève chez Ford Motor à Windsor, le juge Ivan C. Rand a rendu une décision arbitrale célèbre. L'auteur retrace l'origine de la formule Rand et montre comment celle que Von connaît aujourd'hui a été émasculée de certains de ses éléments essentiels.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Le personnel dans l’entreprise : terminologie - Dion, Gérard (Relations industrielles / Industrial Relations, 1975)
Ainsi que nous l'avions fait dans le dernier numéro de Relations industrielles au sujet des « Mouvements du personnel dans l’entreprise » 1, nous présentons ici les définitions d'un certain nombre de termes relatifs au personnel extraits de notre ouvrage en préparation, le Dictionnaire canadien des relations du travail.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Les entreprises multinationales et la politique sociale - Dion, Gérard (Relations industrielles / Industrial Relations, 1975)
This article reviews "Les entreprises multinationales et la politique sociale" by the Bureau international du travail (Genève).
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Les mouvements du personnel dans l’entreprise – terminologie - Dion, Gérard (Relations industrielles / Industrial Relations, 1975)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Petit dictionnaire de droit québécois et canadien - Dion, Gérard (Relations industrielles / Industrial Relations, 1975)
This article reviews "Petit dictionnaire de droit québécois et canadien" by Me Dominique Pagé.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Recommandations internationales sur les statistiques du travail - Dion, Gérard (Relations industrielles / Industrial Relations, 1975)
This article reviews "Recommandations internationales sur les statistiques du travail" by the Bureau international du travail (Genève).
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Years of Hard Labour - Dion, Gérard (Relations industrielles / Industrial Relations, 1975)
The article reviews the book, "Years of Hard Labour," by Morden Lazarus.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Canadian Industrial Strategy: a comment - Donner, Arthur W.; Lazar, Fred (Relations industrielles / Industrial Relations, 1975)
Assess the elements of a national industrial strategy with emphasis on manufacturing and services.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Eléments de sociologie hospitalière - Dussault, Gilles (Relations industrielles / Industrial Relations, 1975)
This article reviews "Eléments de sociologie hospitalière" by Paul Swertz.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Le travail dans l’entreprise et la société modernes - Dussault, Gilles (Relations industrielles / Industrial Relations, 1975)
This article reviews "Le travail dans l’entreprise et la société modernes" created under the direction of Pierre Morin.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Consult and Advise : A History of the National Joint Council of the Public Service of Canada, 1944-1974 - Gillespie, A. Gray (Relations industrielles / Industrial Relations, 1975)
This article reviews "Consult and Advise : A History of the National Joint Council of the Public Service of Canada, 1944-1974" by L.W.C.S. Barnes.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Public Service Staff Relations Board - Gillespie, A. Gray (Relations industrielles / Industrial Relations, 1975)
This paper is primarily an attempt to describe the organization, functions, and influence of the neutral third-party agency in the Federal Public Service collective bargaining system.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Le rapport Waisberg - Hébert, Gérard (Relations industrielles / Industrial Relations, 1975)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Management Science – How Goes Its Philosophy - Howard, J. W. (Relations industrielles / Industrial Relations, 1975)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Task Specialization and Organizational Commitment: An Empirical Examination Among Blue-Collar Workers - Jamal, Muhammad (Relations industrielles / Industrial Relations, 1975)
The present study was undertaken to examine empirically the proposition that specialization in jobs negatively affects the organizational commitment of industrial blue-collar workers. The field work for this study was done among 377 production workers in six companies in Vancouver, British Columbia. The analysis of the data indicated clearly that workers in highly specialized jobs tended to be less committed to their employing organization than workers working on less specialized jobs. In addition, it was observed that task repetition and task simplification were, respectively, inversely related to workers' willingness to exert effort for the success of the employing organization and to workers* desire to remain in the employing organization for an indefinite period of time.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Wage Differentials and Market Imperfections: Some Cross Section Results in Canadian Manufacturing Industries - Jones, John C. H.; Laudadio, Leonard (Relations industrielles / Industrial Relations, 1975)
The purpose of this paper is to analyse the extent to which factor and product market imperfections are responsible for wage differentials. The conclusion is that without some form of factor market imperfection, the existence of imperfection in the product market cannot explain wage differentials.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Les systèmes d’information aux fins de gestion - Ladouceur, Jean (Relations industrielles / Industrial Relations, 1975)
This article reviews "Les systèmes d’information aux fins de gestion" by Rolland Hurtubise.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Personnel Management, A Situational Approach - Ladouceur, Jean (Relations industrielles / Industrial Relations, 1975)
This article reviews "Personnel Management, A Situational Approach" by David P. Crane.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Personnel Management, Reaching Organizational and Human Goals - Ladouceur, Jean (Relations industrielles / Industrial Relations, 1975)
This article reviews "Personnel Management, Reaching Organizational and Human Goals" by Joseph P. Yaney.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Naked Manager - Larocque, Alain (Relations industrielles / Industrial Relations, 1975)
This article reviews "The Naked Manager" by E. Dichter.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Inventaire de satisfaction au travail : validation - Larouche, Viateur (Relations industrielles / Industrial Relations, 1975)
L'auteur présente la démarche suivie pour valider l'Inventaire de Satisfaction au Travail (IST). Le développement de l'Inventaire y est relaté ainsi qu'une description de la version retenue pour fin de validation. Administré à deux groupes de travailleurs (infirmières et contremaîtres), l'auteur explique comment l'instrument a été utilisé ainsi que la signification et la façon de calculer les scores sur les différentes échelles de l'Inventaire de Satisfaction. Il analyse également les résultats obtenus à la suite des tests de stabilité, validité et fidélité.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

L’insécurité d’emploi des travailleurs de la construction au Québec – un mythe ou une réalité? - LeBon, Jean (Relations industrielles / Industrial Relations, 1975)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Pros and Cons - Levine, Gilbert (Relations industrielles / Industrial Relations, 1975)
In this paper, the author examines some of the pros and cons of collective bargaining in University faculties.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Objectifs économiques et indicateurs sociaux - Masson, Claude (Relations industrielles / Industrial Relations, 1975)
This article reviews the report "Objectifs économiques et indicateurs sociaux" by the Conseil économique du Canada.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Effects of Job Design on Turnover, Absenteeism and Health - Mikalachki, A. (Relations industrielles / Industrial Relations, 1975)
The purpose of this article is to show how the deleterious consequences of personnel turnover, absenteeism, and occupational illness are related to job designs which are inappropriate to the needs of workers.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

On the Relationship Between Job Involvement and Central Life Interest - Mitchell, Vance F.; Baba, Vishwanath; Epps, Timothy (Relations industrielles / Industrial Relations, 1975)
The present study investigates the relationship between job involvement (JI) and central life interest (CLI) for a sample of automobile workers chosen from three organizational levels containing unskilled employees, skilled workmen and fore-men. Possible associations of job involvement and work as the« Central Life Interest » with job levels in the occupational hierarchy, age of the individuals and the length of employment were also explored. The results disconfirmed the hypothesized positive relationship between JI and CLI. In fact a low but significant negative relationship was obtained between JI and CLI. Job levels, age and length of employment were found to hâve negligible influence on both JI and CLI. On the basis of the obtained results, directions for future research are indicated.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Au-delà des frontières - Nappi, Carmine (Relations industrielles / Industrial Relations, 1975)
This article reviews "Au-delà des frontières" by le Conseil Économique du Canada (Ottawa).
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Relative Wage Differentials in Canadian Industries - Phillips, Paul (Relations industrielles / Industrial Relations, 1975)
This article reviews "Relative Wage Differentials in Canadian Industries" by Pradeep Kumar.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Les restrictions des prix et des salaires du Ministre Turner - Proulx, Pierre-Paul (Relations industrielles / Industrial Relations, 1975)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Inflation et fiscalité - Raynauld, André (Relations industrielles / Industrial Relations, 1975)
Nous vivons dans une inflation, qui apparaît de plus en plus comme étant la fille naturelle de la croissance, sa seconde nature. Dans ce contexte, l'analyse des politiques de l’après-guerre montre la nécessité d'avoir recours à de nouveaux instruments.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Employement and Earning Inadequacy : A New Social Indicator - Rondeau, Claude (Relations industrielles / Industrial Relations, 1975)
This article reviews "Employement and Earning Inadequacy : A New Social Indicator" by Sar A. Levitan and Robert Taggart III.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Hidden Unemployement by Age and Sex in Canada : 1957-1970 - Ruggeri, Giuseppe C. (Relations industrielles / Industrial Relations, 1975)
This study presents yearly estimates of hidden unemployment and job requirements for full employment in Canada by age and sex for the period 1957 to 1970. The method employed in deriving these estimates involved the calculation of the potential labour force, total and by specific age-sex groups, and the formulation of a relationship relating group employment to total employment.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

A Decade of Manpower Training and Development - Sexton, Jean (Relations industrielles / Industrial Relations, 1975)
This article reviews "A Decade of Manpower Training and Development" by Garth L. Mangum and John Walsh.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Career Education - Sexton, Jean (Relations industrielles / Industrial Relations, 1975)
This article reviews "Career Education" by August C. Bolino.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Counter Point : The Changing Employement Service - Sexton, Jean (Relations industrielles / Industrial Relations, 1975)
This article reviews "Counter Point : The Changing Employement Service" by Miriam Johnson.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Manpower Planning for Local Labor Markets - Sexton, Jean (Relations industrielles / Industrial Relations, 1975)
This article reviews "Manpower Planning for Local Labor Markets" by Garth L. Mangum and David Snedeker.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Public Policy and Manpower Development - Sexton, Jean (Relations industrielles / Industrial Relations, 1975)
This article reviews "Public Policy and Manpower Development" by John W. Holland and Michael L. Skolnik.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Sécurité sociale - Sexton, Jean (Relations industrielles / Industrial Relations, 1975)
This article reviews "Sécurité sociale" by J. Ghestin.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Economics of Labor and Collective Bargaining - Sexton, Jean (Relations industrielles / Industrial Relations, 1975)
This article reviews "The Economics of Labor and Collective Bargaining" by William H. Miernyk.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Structure and Function of Israeli Employers’ Associations - Shirom, Arie; Jacobson, Dan (Relations industrielles / Industrial Relations, 1975)
The first part of this article is devoted to a brief description of the ideological, political, economic and legal environment of the employers' associations in Israel. Then, the current structures of the three major associations are discussed, and their external and internal relations are analyzed. Finally, some tentative conclusions emanating from the report are presented, and several possible implications of the Israeli experience for employers' associations in other countries are suggested.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Guaranteed Annual Income : An Integrated Approach - Smith, Douglas A. (Relations industrielles / Industrial Relations, 1975)
This article reviews "Guaranteed Annual Income : An Integrated Approach" from the Papers and Proceedings of the Nuffield Canadian Seminar (Ottawa).
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Economics of Bargaining Rights in the Fisheries of Nova Scotia and Atlantic Canada - Steinberg, Charles (Relations industrielles / Industrial Relations, 1975)
This paper contends that the legal precedents which have until so recently discouraged positive Canadian legislation, and which could still invalidate fresh legislative efforts, are based on an outdated view of the economic relations of fishermen and fish buyers. The following briefly examines the economic underpinnings of the Canadian fishermen's right to bar gain, with special reference to Nova Scotia and Atlantic Canada.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Final Position Arbitration and Intertemporal Compromise : The University of Alberta Compromise - Swimmer, Gene (Relations industrielles / Industrial Relations, 1975)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Relationship Between Public and Private Sector Wages in Alberta - Swimmer, Gene; Williams, C. B. (Relations industrielles / Industrial Relations, 1975)
The purpose of this study is to determine the nature and magnitude of any relationship between wage and salary changes in specified occupational classifications within the Alberta Civil Service and wage and salary changes in similar occupational classes in Alberta industry. In particular, the possibility of the « leader » role that public service wage and salary changes may play in the determination of occupational wage and salaries in other employment sectors within the Province of Alberta will be articulated.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Contemporary Issues in Canadian Personnel Administration - Thériault, Roland D. (Relations industrielles / Industrial Relations, 1975)
This article reviews "Contemporary Issues in Canadian Personnel Administration" by H. C. Jain.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Managerial Attitudes Toward Industrial Relations : A U.S.-Canadian Comparison - Thompson, Mark; Moore, Larry F. (Relations industrielles / Industrial Relations, 1975)
This paper analyses possible differences in managerial attitudes toward unionism and collective bargaining in Canada and the United States. Divergent patterns of attitudes emerge that are consistent with other observable differences between Canadian and U.S. industrial relations.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Classroom Collective Bargaining Simulation : How Close to the Real Thing - Tracy, L.; Peterson, R. B. (Relations industrielles / Industrial Relations, 1975)
The use of games and simulations as means of instruction is particularly appropriate to a behavioral process such as collective bargaining. The author describes, analyses and evaluates one which is used at the University of Washington.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Determinants of the Demand for Manpower Training : Some Empirical Results - Truesdell, L. R. (Relations industrielles / Industrial Relations, 1975)
The author develops a short-run model for the demand of manpower training. It is shown that the short-run demand for manpower training is sensitive to the levels of unemployment as well as to seasonal factors. Various functional forms are also investigated.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Teacher’s Salary Differentials and the Quality of Educational Services : Recent Developments in Saskatchewan - Walmsley, P. Y.; Ohtsu, M. (Relations industrielles / Industrial Relations, 1975)
This paper examines the relationship between teacher wage determination and the distribution of teacher skill-mix, based on recent Saskatchewan data. The authors argue that while centralized bargaining produces more uniform wage scale throughout the Province, it does not necessarily lead to the uniform distribution of teacher skill-mix among municipalities which is one of the most important conditions for the achievement of equality in the provision of educational services ; rather, it is the ability to pay of the individual school boards which has crucial bearings upon the composition of teacher skill-mix.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Canadian Experiment with Voluntary Incomes Restraint, Degree of Labour Organization and Cyclical Sensitivity of Employement - Walsh, William D. (Relations industrielles / Industrial Relations, 1975)
This paper provides a measure of the industrial distribution of the employment impact of monetary and fiscal policies and suggests that organized labour could have expected to have realized very little differential employment benefits from the Commissions package of proposals— prices and incomes restraint in combination with less monetary and fiscal restraint than would otherwise be possible.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Unions as Complex Organizations : Strategy, Structure and the Need for Administrative Innovation - Warner, Malcolm (Relations industrielles / Industrial Relations, 1975)
This paper reports the attempt to extend the theory and method to the organizational structure of occupational interest associations in order to remedy the lacuna in this important area of comparative research namely trade unions and similar bodies.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

A Note on Manpower Forecasting - Weiermair, K. (Relations industrielles / Industrial Relations, 1975)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Participation aux décisions et négociation collective - Weiss, Dimitri (Relations industrielles / Industrial Relations, 1975)
Dans cet article, l'auteur examine la négociation collective et souhaite la prise en considération de l'entreprise comme un système de négociation : l’étude de la pratique de la négociation collective au sein des grandes organisations aurait beaucoup à gagner, selon l'auteur, d'un rapprochement des théoriciens des organisations et de ceux des relations industrielles.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Relations industrielles et science politique - Weiss, Dimitri (Relations industrielles / Industrial Relations, 1975)
Dans cet article, l'auteur tente d'établir, dans une optique européenne avec un regard particulier à la situation italienne, les liens existant entre le domaine des études des relations industrielles et la science politique.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Collective Bargaining and Academic Freedom : Are they Compatible? - Woods, H. D. (Relations industrielles / Industrial Relations, 1975)
In this paper, the author supports the idea that collective bargaining presents some real dangers to academic freedom on the campuses of Canadian Universities.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Labour Relations in the Public Service : Manitoba - Woods, H. D. (Relations industrielles / Industrial Relations, 1975)
In reference with the Manitoba Labour-Management Review Committee, the author deals with the problem of public employment labour relations and the use of the Review Committee as a device to explore a major public policy problem in industrial relations.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Development of Collective Bargaining in the Toronto Printing Industry in the Nineteenth Century - Zerker, Sally (Relations industrielles / Industrial Relations, 1975)
Analysts of collective bargaining have tended to stress predominant functional characteristics, in general classed as marketing, governmental, and managerial theories. Less emphasis has been placed on the importance of power relationships between organizations. A careful review of the development of collective bargaining in the Toronto printing industry in the nineteenth century suggests that the latter is the most significant factor in the historical process.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z